2016
DOI: 10.1111/ene.13037
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of self‐regulated modified constraint‐induced movement therapy in sub‐acute stroke patients

Abstract: A combination of SR and mCIMT could produce an added effect in functional regain in patients post stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Therefore, the children received the SRL intervention might have enhanced school-related functions. These findings concur with previous studies (15,16,39) that demonstrated an improvement in daily functioning after self-regulation had been implemented. Learning skills, while monitoring difficulties and applying problem-solving strategies, assists with improving self-awareness and motivation to learn, leading to success in task performance.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the children received the SRL intervention might have enhanced school-related functions. These findings concur with previous studies (15,16,39) that demonstrated an improvement in daily functioning after self-regulation had been implemented. Learning skills, while monitoring difficulties and applying problem-solving strategies, assists with improving self-awareness and motivation to learn, leading to success in task performance.…”
Section: Resultssupporting
confidence: 92%
“…Self-regulated learning (SRL) has been shown to enhance individuals' participation in daily activities as a result of underlying psychological, cognitive or sensory-motor problems (14)(15)(16). SRL originates from Albert Bandura's social-cognitive theory (17), involving self-monitoring and self-modification of one's behavior (18).…”
Section: Introductionmentioning
confidence: 99%
“…Two RCTs exploring the benefits of Constraint induced movement therapy (CIMT) upon older stroke survivors were identified [ 32 33 ]. Both were conducted using rehabilitative outpatient departments, but one was conducted in Taiwan [ 33 ] and the other in China [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The IADL scale has good psychometric properties including test-retest reliability [ 38 , 39 ]. The IADL scale has been sensitive to change after constraint-induced movement therapy in stroke survivors [ 40 ]. Furthermore, cognitive impairment before enrollment in stroke rehabilitation could predict IADL scores at 6 months follow-up [ 41 ].…”
Section: Methodsmentioning
confidence: 99%